Towards low-carbon and net-zero energy temperature control in winter cricket farming using a hybrid PV/T–heat pump system - Panuwit Puttaraksa; Thanyaluk Sundach; Sulaksana Mongkon; Chawaroj Jaisin; Sarawut Polvongsri (International Journal of Renewable Energy Development, 2026)
This study evaluated the integration of a photovoltaic–thermal (PV/T) system with a heat pump (HPs) to reduce energy consumption and carbon intensity in a community-scale cricket farming facility during the winter season. Two configurations were compared: a conventional HPs-only system and a hybrid HPs–PV/T system maintaining the rearing temperature at 28–30 °C. In the hybrid setup, a 10.8 kWth heat pump served as the main heating unit, while eight 550 Wp PV/T panels supplied supplementary heat and electricity. The system performance was experimentally assessed, yielding an average heat-pump Coefficient of Performance (COP) of 3.13 and a PV/T performance ratio (PR) of 0.90 under winter conditions. The hybrid system reduced grid-electricity use to 1.58 kWh/day compared with 24.37 kWh/day in total consumption, achieving a 95.4% grid electricity displacement. Annually, the PV/T array generated 7,570.63 kWh of renewable energy—exceeding the total electricity demand of 7,369.07 kWh/yr. The organizational carbon-footprint analysis showed emissions declined from 5,025.98 kg CO₂e to 1,525.83 kg CO₂e, a 69 % reduction. Overall, the HPs–PV/T hybrid configuration proved to be an energy-efficient, low-carbon solution for temperature-controlled insect farming, particularly suitable for small- and community-scale applications.